Strategies to Increase Customer Satisfaction and Change Consumer Behavior towards Brands - Ratna Ghosal; Balaji Prakash (Journal of Current Research In Multidisciplinary, 2023)
This research aims to see what factors influence the level of customer satisfaction when shopping in retail. From the measurements that have been carried out, the results show that 80% of the indicators selected as benchmarks for brand performance show a large gap between the performance value and its importance. Where it is found that Q1 (cashier performance in serving) has the greatest value of -1.6. Followed by the Q6 indicator (convenience in shopping areas) with a value of -0.767. Furthermore, many respondents also thought that the Q3 indicator (employees' understanding of the product and the ability to provide reliable information) was quite bad, with a gap value of -0.567. Then there are 2 indicators that show the same gap value, namely Q2 (employee consistency when offering promos) and Q7 (products available in stores), with a gap value of -0.5. It was found that there are 4 indicators that fall into quadrant 1, namely indicators Q1 (cashier performance in serving), Q6 (comfort of the shopping area), Q3 (employees' understanding of the products being sold and their ability to provide reliable information), and Q9 (physical evidence at the store). The inclusion of 4 out of 10 of these indicators into quadrant 1 indicates that the store failed to provide good and satisfactory performance to consumers, while the other 4 indicators are considered very important with importance values of Q1 4,667, Q6 4,367, Q3 4.2, and Q9 4,033 out of 5 points.